DILEMMAS IN THE DIFFERENTIAL DIAGNOSIS OF PEDIATRIC MULTIPLE SCLEROSIS: Dilemmas in the differential diagnosis of POMS - Drulovic, Prof. Jelena; Jančić, Jasna; Nikolić, Blažo; Pekmezovic, Tatjana; Mesaroš, Šarlota (Medical Research, 2025)
Multiple sclerosis (MS) is a chronic, inflammatory and neurodegenerative disease of the central nervous system (CNS). It typically presents in early or middle adulthood, and pediatric-onset MS (POMS), defined by a first MS attack occurring before age 18 years, is less common. Current data from the Danish Multiple Sclerosis Registry, indicates that nearly 3% had onset before age 18 years. In comparison to adult-onset MS, POMS patients typically have a more inflammatory-active disease course, resulting in more frequent relapses, but slower long-term disability accumulation. In POMS, diagnostic dilemmas may include differentiating MS from acute disseminated encephalomyelitis (ADEM) and myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD), both of which most commonly occur among children and share some clinical and imaging features with MS. Inherited leukodystrophies might also be considered in differential diagnosis only in certain cases, because their clinical characteristic is progressive disease course, uncommon for other above-mentioned acquired demyelinating syndromes, including neuromyelitis optica spectrum disorder. It has to be kept in mind that magnetic resonance imaging of brain and spinal cord are crucial for establishing timely and correct diagnosis of POMS, after excluding alternative diagnosis, enabling starting immediate effective treatment.